Emigration from Mexico and the peso devaluation: unveiling of a myth - Bustamante, Jorge A. (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
In this article, the author analyzes the results of two statistical researches on the influx of undocumented Mexicans to the United States in order to dismantle the supposed relation ship, defended by northamerican public and political instances, between the devaluation of the mexican peso which occurred on december 19th, 1994, and the increase of these inflows. Migration from Mexico to the United States is conceived as a circular process in which individuals move to and fro between two countries, both in legal and undocumented ways, pushed by the interplay of supply and demand, thus building up a social bond formed by the processes of interactions between mexicans and U.S. nationals within the framework of a relationship related to labour